Pengaruh Literasi Hukum terhadap Minat Tawuran Siswa SMK Swasta Dwiwarna Medan - Anwar Sulaiman Nasution; Agus Salim Harahap; Yessi Kurnia Arjani Manik (Journal on Education, 2024)
The lack of legal literacy in certain groups of society will have a negative impact on the stability of social relations. The phenomenon of brawls between students continues to occur from time to time due to high interest among the students themselves. The perpetrators of the brawl can be charged with several laws and regulations, such as Article 170 of the Criminal Code. Therefore, research was carried out with the aim of finding out how the influence of legal literature on the brawl interest of SMK Dwiwarna Medan students. Type of quantitative research with a descriptive approach. The research instrument uses questionnaires. The data analysis technique uses simple linear regression with the help of SPSS soft ware version 24. The results of the study stated that legal literacy had a negative but significant effect on the interest in brawls in students of SMK Swasta Dwiwarna Medan. If legal literacy is improved, the interest in brawls in students of SMK Swasta Dwiwarna Medan will decrease significantly.